Corn Milk Yoghurt: Nutritional Composition Analysis Based On Fermentation Starter Variatons - Burhan, Abd Rukman; Firmansyah, Firmansyah (Journal of Agriculture, 2025)
This study explores the nutritional profile of corn milk yoghurt developed using different fermentation starters. Corn (Zea mays L.), rich in carbohydrates, protein, and essential micronutrients, offers a sustainable and affordable plant-based alternative to dairy in yoghurt production. With increasing consumer demand for functional, health-promoting foods and the challenges of animal milk availability, corn milk presents a promising base for fermented products. This experimental research applied a Completely Randomized Design (CRD) with four treatments: Lactobacillus bulgaricus, Lactobacillus casei, a combination of both, and a control (no starter). The objective was to evaluate the impact of starter variation on lactic acid content, protein concentration, and fat levels in the resulting yoghurt. Findings revealed that the combined culture produced the highest lactic acid level (0.7%), while yoghurt fermented solely with L. bulgaricus yielded the highest protein content (3.6%) and the lowest fat content (1.05%). Although the lactic acid content fell below the Indonesian National Standard (SNI) threshold, all yoghurt variants met the SNI minimum for protein and were classified as low-fat yoghurts. These outcomes indicate that fermentation starter selection significantly influences the nutritional characteristics of corn milk yoghurt. Moreover, the study demonstrates the potential of corn milk as a functional food base that aligns with both nutritional standards and sustainable food innovation. L. bulgaricus emerged as the most effective starter, optimizing both protein enrichment and fat reduction. These insights may guide future development of non-dairy fermented products for health-conscious and lactose-intolerant populations.